Do cyber-birds flock together? Comparing deviance among social network members of cyber-dependent offenders and traditional offenders - Weulen Kranenbarg, Marleen (European journal of criminology, 2021)
The distinct setting in which cyber-dependent crime takes place may reduce the similarity in the deviance of social network members. We test this assumption by analysing the deviance of the most important social contacts of cyber-dependent offenders and traditional offenders in the Netherlands (N = 344 offenders; N = 1131 social contacts). As expected, similarity in deviance is weaker for cyber-dependent crime. Because this is a strong predictor of traditional offending, this has important implications for criminological research and practice. Additionally, for both crime types the offending behaviour of a person is more strongly linked to the deviance of social ties if those ties are of the same gender and age, and if the offender has daily contact with them. Implications and future criminological research suggestions are discussed.